IMPLEMENTASI 24 PROFIL LEADERSHIP CURRICULUM DI SDIT AR-RAHMAH MAKASSAR - Jusria Kadir; Dewi Saputri (Balai Diklat Keagamaan Jakarta, 2025)
Abstract This article aims to analyze teachers’ understanding and practice in implementing the 24 Profiles of Leadership Curriculum at SDIT Ar-Rahmah Makassar. This research is an evaluation study employing a sequential explanatory model as its research approach. The research was conducted at SDIT Ar-Rahmah Makassar for one year (11/23-10/2024). The results showed that: 1) Teachers’ understanding showed high (53.6%) and medium (46.4%) categories. 2) The practice of spiritual values shows a high category (100%), the practice of academic competencies shows a high category (57.1%) and moderate (42.9%), the practice of leadership characters shows a high category (57.1%) and moderate (42.9%), and the practice of leadership competencies shows a high category (85.7%) and moderate (14.3%). 3) Teachers’ understanding and practice are influenced by several factors that both support and hinder them. Supporting factors include teacher competence, effective school management, various extracurricular activities, and parental support. The inhibiting factors are infrastructure facilities, the burden of learning administration, and lack of coordination with parents/guardians. Abstrak Artikel ini bertujuan untuk menganalisis pemahaman dan praktik guru dalam mengimplementasikan 24 Profil Leadership Curriculum (Kurikulum kepemimpinan ) di SDIT Ar-Rahmah Makassar. Penelitian ini merupakan penelitian evaluasi dengan pendekatan penelitian kombinasi model eksplanasi sekuensial. Penelitian dilakukan di SDIT Ar-Rahmah Makassar selama satu tahun (11/23-10/2024). Hasil penelitian menunjukkan bahwa: 1) Pemahaman guru menunjukkan kategori tinggi (53,6%) dan sedang (46,4%). 2) Praktik spiritual values menunjukkan kategori tinggi (100%), praktik academic competencies menunjukkan kategori tinggi (57,1%) dan sedang (42,9%), praktik leadership characters menunjukkan kategori tinggi (57,1%) dan sedang (42,9%), dan praktik leadership competencies menunjukkan kategori tinggi (85,7%) dan sedang (14,3%). 3) Pemahaman dan praktik guru didukung dan dihambat oleh beberapa faktor. Faktor pendukungnya ialah kompetensi guru, manajemen sekolah, aneka kegiatan/ekstrakurikuler, dan suportivitas orang tua/wali murid. Adapun faktor penghambatnya adalah sarana prasarana, beban administrasi pembelajaran, dan koordinasi yang kurang dengan orang tau/wali murid.